Tooth development included in the multifocal jaw lesions of langerhans cell histiocytosis - T. MITOMI, M. TOMIZAWA & T. NODA (Paediatric Dentistry, 2005)
Langerhans cell histiocytosis (LCH), formerly known as Histiocytosis X, is characterized by an abnormal proliferation of histiocytes of unknown cause.